2022
DOI: 10.1182/blood.2021015106
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of LCK tyrosine kinase and mTOR signaling in T-cell acute lymphoblastic leukemia

Abstract: Relapse and refractory T cell acute lymphoblastic leukemia (T-ALL) has a poor prognosis and new combination therapies are sorely needed. Here, we used an ex vivo high-throughput screening platform to identify drug combinations that kill zebrafish T-ALL and then validated top drug combinations for preclinical efficacy in human disease. This work uncovered potent drug synergies between AKT/mTORC1 inhibitors and the general tyrosine kinase-inhibitor, dasatinib. Importantly, these same drug combinations effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 94 publications
0
23
0
1
Order By: Relevance
“…Moreover, NOTCH1 regulates the phosphorylation of multiple signaling proteins of the mTOR pathway through a PI3K/AKT-independent but MYC-dependent mechanism [ 212 ]. mTOR is an essential regulator of T-ALL cell growth, and its inhibition has been demonstrated to have anti-leukemic effects either alone or in combination with other drugs [ 106 , 213 , 214 , 215 , 216 , 217 , 218 , 219 ]. Notably, dual inhibition of NOTCH1 and mTOR signaling was proved to act synergistically by blocking T-ALL proliferation in vitro [ 106 ].…”
Section: Molecular Collaborators Of Notch1 Signaling In T-all Pathoge...mentioning
confidence: 99%
“…Moreover, NOTCH1 regulates the phosphorylation of multiple signaling proteins of the mTOR pathway through a PI3K/AKT-independent but MYC-dependent mechanism [ 212 ]. mTOR is an essential regulator of T-ALL cell growth, and its inhibition has been demonstrated to have anti-leukemic effects either alone or in combination with other drugs [ 106 , 213 , 214 , 215 , 216 , 217 , 218 , 219 ]. Notably, dual inhibition of NOTCH1 and mTOR signaling was proved to act synergistically by blocking T-ALL proliferation in vitro [ 106 ].…”
Section: Molecular Collaborators Of Notch1 Signaling In T-all Pathoge...mentioning
confidence: 99%
“…Lck inhibitors, such as dasatinib and SJ11646, showed efficacy against T‐acute lymphoblastic leukaemia in preclinical studies and in patients with T‐acute lymphoblastic leukaemia (Hu et al, 2022). Recent important studies have shown that the combination of temsirolimus and dasatinib treatment will be efficacious for a large fraction of human T‐acute lymphoblastic leukaemias (Laukkanen et al, 2022). Together, Lck inhibitors are promising therapeutic agents in T‐acute lymphoblastic leukaemia and other cancers.…”
Section: Potential Therapeutic Approaches and Targetsmentioning
confidence: 99%
“…Upon dasatinib treatment, phosphorylation of the Lck substrate Zap-70 decreased, and secretion of cytokines including IL-2, TNF-α, and IFN-γ was also rapidly abolished (Lee et al, 2010;Leclercq et al, 2021). Dasatinib is also indicated for T-ALL treatment through inhibiting Lck function by interrupting downstream propagation of TCR signals, thus leading to suppression of cell proliferation (Laukkanen et al, 2022). In addition, Han et al (2014) found that dasatinib could significantly inhibit migration of glioma stem cells.…”
Section: Lck-nf-κb Signaling In Solid Cancersmentioning
confidence: 99%